Pengembangan Aplikasi Geotagging Pelaporan Keluhan Masyarakat pada Dinas Perhubungan Kota Mojokerto menggunakan Restful Web Services berbasis Mobile - Nizar Rahman Kusworo; Achmad Arwan; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Transportation Department of Mojokerto City is one of the Regional Work Unit of the Mojokerto City Government whose task is to serve road use permits, carry out community satisfaction surveys and receive complaints regarding various problems that occur in the field of transportation and traffic. Problems related to tasks such as the existence of people who are reluctant to carry out road use permits, the difficulty of the process of distributing community satisfaction survey questionnaires and complaints from the public make the Transportation Department of Mojokerto City overwhelmed. To overcome these problems in this study an application was developed for the community to take care of road use permits, fill out a community satisfaction survey online and be able to report their complaints through a smartphone with the waterfall development method. Applications built with hybrid technology use NodeJS as a back-end, VueJS as a front-end framework combined with Framework7 that provides components to get a feel of native applications and Apache Cordova that functions to package applications as packages using the Software Development Kit (SDK). This application aims to provide maximum service both in road use permits, community satisfaction surveys and complaints. The results of the study were then tested using unit testing, integration testing, validation testing and compatibility testing which produced 100% valid on each test so that it can be said the system was in accordance with the results of engineering needs and design.